Biofilm growth of Chlorella sorokiniana in a rotating biological contactor based photobioreactor. Issue 12 (5th August 2014) - Blanken, W.; Janssen, M.; Cuaresma, M.; Libor, Z.; Bhaiji, T.; Wijffels, R. H.
ABSTRACT Microalgae biofilms could be used as a production platform for microalgae biomass. In this study, a photobioreactor design based on a rotating biological contactor (RBC) was used as a production platform for microalgae biomass cultivated in biofilm. In the photobioreactor, referred to as Algadisk, microalgae grow in biofilm on vertical rotating disks partially submerged in a growth medium. The objective is to evaluate the potential of the Algadisk photobioreactor with respect to the effects of disk roughness, disk rotation speed and CO2 concentration. These objectives where evaluated in relationship to productivity, photosynthetic efficiency, and long‐term cultivation stability in a lab‐scale Algadisk system. Although the lab‐scale Algadisk system is used, operation parameters evaluated are relevant for scale‐up. Chlorella Sorokiniana was used as model microalgae. In the lab‐scale Algadisk reactor, productivity of 20.1 ± 0.7 g per m2 disk surface per day and a biomass yield on light of 0.9 ± 0.04 g dry weight biomass per mol photons were obtained. Different disk rotation speeds did demonstrate minimal effects on biofilm growth and on the diffusion of substrate into the biofilm. CO2 limitation, however, drastically reduced productivity to 2–4 g per m2 disk surface per day. Productivity could be maintained over a period of 21 weeks without re‐inoculation of the Algadisk. Productivity decreased under extreme conditions such as pH 9–10, temperature above 40°C, and with low CO2 concentrations. Maximal productivity, however, was promptly recovered when optimal cultivation conditions were reinstated. These results exhibit an apparent opportunity to employ the Algadisk photobioreactor at large scale for microalgae biomass production if diffusion does not limit the CO2 supply. Biotechnol. Bioeng. 2014;111: 2436–2445. © 2014 Wiley Periodicals, Inc.